Effects of nitrogen fertilization and seasons on the morphogenetic and structural characteristics of Piatã (Brachiaria brizantha) grass - Farias, Lorraine do Nascimento; Zanine, Anderson de Moura; Ferreira, Daniele de Jesus; Ribeiro, Marinaldo Divino; de Souza, Alexandre Lima; Valério Geron, Luiz Juliano; Araujo Pinho, Ricardo Martins; Santos, Edson Mauro (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
The objective of this study was to evaluate the morphogenetic and structural characteristics of Piatã grass under rotational stocking and nitrogen fertilization during the seasons. A randomized complete block design in a split-plot arrangement with three replications was used. The main plots were the applications of 0, 150, 300 and 450 kg per ha of N in the form of urea, and the subplots were seasons of the year: late summer/fall, winter, spring and summer. No interaction was detected between nitrogen fertilization and season for leaf appearance rate, leaf lifespan, number of live leaves and final length leaves. However, an interaction (P<0.05) of nitrogen fertilization and season influenced leaf elongation rate, phyllochron, leaf senescence rate and stem elongation rate. The leaf elongation rate and leaf appearance rate were linearly affected (P<0.05) by nitrogen fertilization. The seasons affected (P<0.05) the leaf lifespan and number of life leaves. The leaf lifespan decreased by 0.06 days for each kg of N applied. On the other hand, the number of live leaves increased by 0.0026 leaves/tiller for each kg of N. Fertilization with nitrogen positively affects morphogenetic and structural characteristics of Piatã grass under rotational stocking. This effect can be optimized during rainy periods in spring and late summer/autumn.